2017
DOI: 10.1038/ncomms14257
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus particles induce centrosome amplification and chromosomal instability

Abstract: Infections with Epstein–Barr virus (EBV) are associated with cancer development, and EBV lytic replication (the process that generates virus progeny) is a strong risk factor for some cancer types. Here we report that EBV infection of B-lymphocytes (in vitro and in a mouse model) leads to an increased rate of centrosome amplification, associated with chromosomal instability. This effect can be reproduced with virus-like particles devoid of EBV DNA, but not with defective virus-like particles that cannot infect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 68 publications
2
71
0
2
Order By: Relevance
“…LMP1-associated genomic instability may also result from telomerase activation and DNA damage response (DDR) inhibition [69, 77]. Intriguingly, EBV tegument protein BNRF1 could also induce centrosome amplification and further chromosome instability during lytic infection, suggesting that EBV viral particles may be sufficient to modify host chromosome without the establishment of latent infection [78]. …”
Section: Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
“…LMP1-associated genomic instability may also result from telomerase activation and DNA damage response (DDR) inhibition [69, 77]. Intriguingly, EBV tegument protein BNRF1 could also induce centrosome amplification and further chromosome instability during lytic infection, suggesting that EBV viral particles may be sufficient to modify host chromosome without the establishment of latent infection [78]. …”
Section: Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
“…EBV‐infected cells express viral oncogenes that induce cell transformation. EBV latent and lytic genes can cause chromosomal instability . As seen in many cancers, multiple genetic alterations are present in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…EBV latent and lytic genes can cause chromosomal instability. [2][3][4][5][6] As seen in many cancers, multiple genetic alterations are present in NPC. Early studies identified the losses of chromosomes 3p and 9p as early events in the development of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Also, EBV lytic genes BZLF1 , BGLF4 and BGLF5 can induce genome instability. Most notably, one latest research reported EBV lytic replication had a marked influence on the genetic stability and identified a new mechanism in EBV induced cancer . EBV virions that generate in the process of lytic replication can induce aneuploidy and centrosome amplification, associated with chromosomal instability, thereby conferring a risk to non‐replicating cells and for development of tumors.…”
Section: Oxidative Stress and Ebv Lytic Reactivationmentioning
confidence: 99%